Theoretical Paradigm and Empirical Perspective of the “Slumdog Millionaire Effect” - Akthar, Shamima (Atna Journal of Tourism Studies, 2016)
The effect of film-induced tourism has long been known. The worth of films in inducing tourism at international, domestic and regional levels to the destination featured, has been proven by researcher‟s time and again. Also, the consumption of these 'screen products' by today's dynamic, curious and knowledgeable tourists has been proven to have a direct influence on his decision-making. Evaluation of specific films in various research projects has validated the existence of sustainable prosperity to the destination. These and many more of such researchbased endorsements and affirmations have given an extra boost to the phenomenon of movie-induced tourism worldwide. The existence of possibly compelling economic value of this strand of tourism is known to all, and therefore, destinations are trying to understand and comprehend the drivers of this phenomenon in order to exploit its benefits. India has a negligible share of its contributions in this field. The statistics concerning directly to the impact of films on tourist numbers are limited. Even though this phenomenon has been well accepted, proclaimed and communicated in India, very few researches of it have been published and made available to the policy makers. To fill some of this void, this research work proposes to analyze the 2008 Golden Globe and Academy Awards winner movie Slumdog Millionaire with a backdrop of film-induced tourism and investigate the post-modern experience of India that has been depicted in the movie. Furthermore, through empirical observation, this work attempts to draw relationships between cause- 'Slumdog Millionaire' and effect – 'India's inbound tourism' related to this phenomenon, and maps out the interrelation of filminduced tourism with India as a destination. This movie has drawn both positive and negative reactions, therefore, an evaluation leading to conclusions and specific recommendations is yet another goal of the proposed work.